2016
DOI: 10.1177/0192623316674274
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in a Murine Model of Air Pollutant–induced Nonatopic Asthma and Rhinitis

Abstract: Ozone is an irritating gas found in photochemical smog. Epidemiological associations have been made between the onset of asthma and childhood exposures to increasing levels of ambient ozone (i.e., air pollutant-induced nonatopic asthma). Individuals, however, vary in their susceptibility to this outdoor air pollutant, which may be due, in part, to their genetic makeup. The present study was designed to test the hypothesis that there are murine strain-dependent differences in pulmonary and nasal pathologic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…The mucous cell metaplasia observed in the surface epithelium lining the proximal axial airway (G5) in the ILC-sufficient mice after repeated 9-day exposure was also similar in character and magnitude to the ozone-induced metaplastic responses that we have previously observed in the nasal (Kumagai et al 2016;Ong et al 2016) and pulmonary airways (Harkema et al 2017) of similarly exposed C57BL/6 mice. Mucous cell metaplasia is a commonly reported nasal epithelial response to repeated daily ozone exposures in rats (Cho, Hotchkiss, and Harkema 1999;Harkema et al 1999) as well as in nonhuman primates Harkema, Plopper, Hyde, St George, Wilson, et al 1987).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The mucous cell metaplasia observed in the surface epithelium lining the proximal axial airway (G5) in the ILC-sufficient mice after repeated 9-day exposure was also similar in character and magnitude to the ozone-induced metaplastic responses that we have previously observed in the nasal (Kumagai et al 2016;Ong et al 2016) and pulmonary airways (Harkema et al 2017) of similarly exposed C57BL/6 mice. Mucous cell metaplasia is a commonly reported nasal epithelial response to repeated daily ozone exposures in rats (Cho, Hotchkiss, and Harkema 1999;Harkema et al 1999) as well as in nonhuman primates Harkema, Plopper, Hyde, St George, Wilson, et al 1987).…”
Section: Discussionsupporting
confidence: 72%
“…We have recently reported that the magnitude of ozone-induced mucous cell metaplasia in the proximal pulmonary airway is strain dependant (Harkema et al 2017). In this previous study, we found that C57BL/6 male mice exhibit greater metaplasia than BALB/c male mice, even though both strains of mice were of similar age and exposed to the same exposure regimen (0.8 ppm ozone, 4 hr/day, for 9 consecutive weekdays, as in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, repeated daily exposures, but not a single-day exposure, to ozone caused type 2 immune responses with associated eosinophilic inflammation in the nasal airways of ILC-sufficient Rag2 À/À and C57BL/6 mice, but not Rag2 À/À Il2rg À/À mice. Though we have reported similar findings previously, 1,3,17 our current study is the first to document ozone-induced influx (mucosal distribution and density) and persistence (postexposure) of GATA-3þ lymphoid cells in the nasal airways of ILC-sufficient, but T-cell and B-cell-deficient Rag2 À/À mice and ILC-, T-cell-and B-cell-sufficient C57BL/6 mice, as well as the absence of these lymphoid cells in air-or ozone-exposed ILC-, T-cell-, and B-cell-deficient Rag2 À/À Il2rg À/À mice.…”
Section: Discussionsupporting
confidence: 90%
“…These O 3induced airway alterations are mediated by ILC2s, rather than by the more classical T and B lymphoid cells that are important in adaptive immune responses typically associated with allergic rhinitis and allergic asthma (103). Furthermore, repeated exposure to O 3 induces ILC2-mediated airway type 2 immunity, eosinophilic inflammation, and mucous cell metaplasia in the pulmonary airways (104,105). Thus, repeated O 3 exposures may induce a nonatopic asthma phenotype characterized by innate type 2 immunity, eosinophilic inflammation, and mucous cell metaplasia.…”
Section: A Mechanism For Nonatopic Asthmamentioning
confidence: 99%